Design of Project-Based Task Management System on Moodle for Computational Thinking Improvement - Aji Tomi Pamungkas, Rizky; Lanang Eka Prismana, I Gusti (Universitas Negeri Surabaya, 2025)
The integration of technology in education through the LMS (Learning Management System) platform can facilitate the management of online learning. It becomes a challenge for teachers to develop more innovative and effective learning methods. Thus, this research develops a Moodle based E-Learning Website that includes a TMS (Task Management System) using a project based learning approach that aims to strengthen students cognitive and psychomotor abilities and improve their computational thinking skills. The ADDIE approach, which consists of the stages of analysis, development, design, implementation, and evaluation, was used to build this website. The results showed that students computational thinking ability was much better by using “Eduframe” E-Learning Website in Bootstrap 5 framework implementation material compared to conventional learning model. Independent t-test showed an increase in students cognitive understanding (post test score of experimental class cognitive: 86,94 > control class: 72,33) and students psychomotor ability (post test score of experimental class psychomotor: 86,94 > control class: 75,06). Compared to conventional learning style. The hypothesis test results also get a Sig. (2-tailed) of 0,001 < 0,05 which states Thus, H0 is rejected, and H1 is accepted, indicating that there are contrasts in the aftereffects of understudies computational thinking skills in web programming subjects after using the “Eduframe” website which includes a TMS (Task Management System) using a project-based learning model for class XI RPL students at SMKN 2 Surabaya.